The Imposition of Criminal Sanctions as an Ultimum Remedium in The Resolution of Consumer Protection Crime - Fithri, Beby Suryani (JURNAL AKTA, 2025)
Consumer protection in Indonesia currently faces significant challenges, particularly regarding weak law enforcement and uncertainty in the application of criminal sanctions. Based on Law No. 8 of 1999 on Consumer Protection, criminal sanctions are applied as Ultimum Remedium, which complicates the process of obtaining justice for consumers who are harmed. This paper proposes a paradigm shift in the application of criminal sanctions by making them the primum remedium in resolving consumer criminal cases. This approach is expected to provide legal certainty, justice, and a deterrent effect on business actors who violate consumer rights. Additionally, the study suggests reconstructing several articles in the Consumer Protection Law, such as Articles 8, 9, 13 paragraph (2), 15, 17, 18, and Articles 62 and 63, to align with the evolving conditions of society, economy, and global trade. These changes aim to enhance the effectiveness of consumer protection and ensure better legal certainty for Indonesian society in the face of global legal developments related to consumer protection.